2017
DOI: 10.1007/s12282-017-0793-9
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA: a novel type of biomarker for cancer

Abstract: Circular RNAs (circRNAs) are a class of long, non-coding RNAs molecules that shape a covalently closed continuous loop which have no 5'-3' polarity and contain no polyA tail. CircRNAs also possess relatively jarless framework and are highly tissue-specific expressed in the eukaryotic transcriptome. Emerging evidences have discovered that thousands of endogenous circRNAs are present in mammalian cells and they mediate gene expression at the transcriptional or post-transcriptional level by binding to microRNAs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
450
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 640 publications
(455 citation statements)
references
References 66 publications
3
450
1
1
Order By: Relevance
“…It was reported that circRNAs regulate the gene expression in both transcriptional and post‐transcriptional process . Recently, circRNAs, novel noncoding RNAs with varied biological functions and pathological implications, have been shown to be closely related with various diseases, including osteoarthritis, atherosclerotic vascular disease risk, neurological disorders, Parkinson's disease, Alzheimer's disease, schizophrenia and so on . However, the roles of circRNAs, as well as circRNA and miRNA axis in the development and progression of OA are little understood.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that circRNAs regulate the gene expression in both transcriptional and post‐transcriptional process . Recently, circRNAs, novel noncoding RNAs with varied biological functions and pathological implications, have been shown to be closely related with various diseases, including osteoarthritis, atherosclerotic vascular disease risk, neurological disorders, Parkinson's disease, Alzheimer's disease, schizophrenia and so on . However, the roles of circRNAs, as well as circRNA and miRNA axis in the development and progression of OA are little understood.…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs are conserved and stable, and numerous circRNAs seem to be specifically expressed in a cell type or developmental stage [7,8]. The progressive stage-and subcellular type-based expression modern indicate that circRNAs may play important roles in the mediation of multiple diseases, including cancer [9,10]. Recently, certain kinds of circRNAs have been found to be significantly deregulated in NSCLC, and these deregulated circRNAs are suggested to participate in cancer development [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is the third leading cause of mortality in the world. With high incidence of metastasis and recurrence, most patients with HCC have a poor prognosis (Fu et al, ; H. D. Zhang, Jiang, Sun, Hou, & Ji, ; Huang et al, ). Patients with HCC can be diagnosed at an early stage and accept chemotherapy with the improvement of diagnostic strategies; however, there were still many patients with HCC who lost the best operation opportunity.…”
Section: Introductionmentioning
confidence: 99%